We ARTogether: A review of the importance of social support through the lens of newcomer women’s mental wellness programming - Levitz, Naomi Ruth; Vega, Hugo (Groupwork, 2020)
This article highlights one approach used to solidify social support and bolster mental wellness for newcomer women through community, arts and connection. Core values of the program are presented along with examples of successful programming that has been experienced by hundreds of newcomer women in Southwestern Ontario. By using a trauma informed lens, staff and participants are able to share lessons and create community. Women were able to come together to learn how to connect across linguistic and cultural divides to unearth shared experiences of womanhood. The precursor to this article was presented at the international social work and social development conference, swsd2018 in Dublin, Ireland.